Formulate mathematical equations to determine the rotation and symmetry (J  ) of planes The energy of the isotope is 54 Xe 132 (Journal of the College of Basic Education, 2023)
In present study, the logarithm values of comparative halftime log(f t ) forenergy levels of Xe 132 isotope yield from decay levels (2.3h(4 + )) of I 32isotope and (6.427d(2 - )) of Cs 132 isotope gets from study Ref. [5] were calculated, also determined values of spin (J) and parity (  ) for levels that ) by using mathematical equations forming +  , - have transition of Beta ( . with statistical package